Healing Effects of Formulations with Extract of Sonchus oleraceus - Nonato, Idelvânia dos Anjos; Vargas Viloria, Marlene Isabel; Carvalho, Gabriel Domingos; Valente, Fabrício Luciani; Salcedo, Joaquín Hernán Patarroyo; da Rosa, Marcelo Barcellos; de Carvalho, Camilo Amaro (Acta Scientiae Veterinariae, 2018)
Introduction: Scar is defined as a process of tissue regeneration characterized by fibroblasts and a disorganized extracellular matrix, formed mainly by collagen. Thus it is understood that regeneration capacity is a phenomenon that occurs in order to repair an injured tissue. However, science has been looking for alternatives to assist in the repair process, and thus phytotherapy has been used as a therapeutic resource in medicine, and scientifically proven its efficiency. The plant Sonchus oleraceus is known, among other names, as “serralha” or sowthistle. It is a cosmopolitan species, found in several agricultural regions infesting crops. In Brazil, it is more frequent to grow in the winter and its seeds can be kept viable for eight years in the soil. This plant can be used as a popular drug for diuretic proposals, in cases of anemia, liver diseases and in cases of treatment of vitiligo in the eastern region of the state of Minas Gerais, Brazil. The objective of this research was to evaluate two different products (ointment and balsam) composed by S. oleraceus in the healing of surgical wounds in rats (Rattus novergicus). Materials, Methods & Results: Sonchus oleraceus specimens were obtained at the beginning of May, during the autumnwinter season, in which there is already a flowering of this plant. The leaves and stem of S. oleraceus were selected, cleaned and dried under study at 40°C of circulating air for four days for complete dehydration, and then ground in a knife mill. The constituents were prepared in 80% alcohol (v / v) and subjected to ultrasonic extraction for 60 min. The hydroalcoholic extract of S. oleraceus was concentrated on a rotary evaporator until all alcohol evaporated and the aqueous extract was obtained. The extracts were produced at concentrations of 5%, 10% and 15% and sent for manipulation of the pharmaceutical formulations of ointment and salve. Forty Wistar rats were divided into eight groups for evaluation of different products (salve and ointment). The wounds were created on the back of the animals and the products were applied daily; for analysis, clinical evaluations and wound measurement were performed daily. After 15 days, a biopsy was performed for histopathological analysis and quantification of type I and III collagen fibers. Measurement of the wound in rats treated with ointment containing 15% of extract presented better tissue retraction, with complete retraction observed after 10 days of treatment. Type I collagen was predominant in all samples; however, the healing properties of the balsam containing 5% extract and ointment containing 5% and 15% extract were significantly different. Discussion: As a conclusion, Sonchus oleraceus influenced the healing process of the skin. This pharmacological action is probably directly related to the amount of flavonoids present in its composition, that is, the higher the extract concentration, the better its efficacy. However, a better efficacy in the ointment is emphasized by better adhesion to the skin. Studies have shown that the flavonoids present in most plants have relevant healing activity, stimulating the proliferation of fibroblasts and the production of collagen, acting on the inhibition of metalloproteinase, thus increasing the rate of synthesized collagen. Other researchers reported a high concentration of flavonoids (anthocyanins and tannins) that act as mediators of inflammation, stimulating the production of inflammatory cytokines and tumor necrosis factor, observed in this species.